Involvement of the CXCL12 System in the Stimulatory Effects of Prenatal Exposure to High-Fat Diet on Hypothalamic Orexigenic Peptides and Behavior in Offspring - Poon, Kinning; Barson, Jessica R.; Shi, Huanzhi; Chang, Guo Qing; Leibowitz, Sarah F. (Frontiers in Behavioral Neuroscience, 2017)
Exposure to a high fat diet (HFD) during gestation stimulates neurogenesis and expression of hypothalamic orexigenic neuropeptides that affect consummatory and emotional behaviors. With recent studies showing a HFD to increase inflammation, this report investigated the neuroinflammatory chemokine, CXCL12, and compared the effects of prenatal CXCL12 injection to those of prenatal HFD exposure, first, by testing whether the HFD affects circulating CXCL12 in the dam and the CXCL12 system in the offspring brain, and then by examining whether prenatal exposure to CXCL12 itself mimics the effects of a HFD on hypothalamic neuropeptides and emotional behaviors. Our results showed that prenatal exposure to a HFD significantly increased circulating levels of CXCL12 in the dam, and that daily injections of CXCL12 induced a similar increase in CXCL12 levels as the HFD. In addition, prenatal HFD exposure significantly increased the expression of CXCL12 and its receptors, CXCR4 and CXCR7, in the hypothalamic paraventricular nucleus (PVN) of the offspring. Finally, the results revealed strong similarities in the effects of prenatal HFD and CXCL12 administration, which both stimulated neurogenesis and enkephalin (ENK) expression in the PVN, while having inconsistent or no effect in other regions of the hypothalamus, and also increased anxiety as measured by several behavioral tests. These results focus attention specifically on the CXCL12 chemokine system in the PVN of the offspring as being possibly involved in the stimulatory effects of prenatal HFD exposure on ENK-expressing neurons in the PVN and their associated changes in emotional behavior.